1989
DOI: 10.1177/154193128903301013
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Research Paradigm for Complex Experimentation

Abstract: Most human factors design problems involve large data spaces with so many factors that a single experiment investigating all of these factors simultaneously is unreasonable. The design of a computer-based telephone inquiry system is presented as an example interface which required consideration of over 100 independent variables which could affect end-user performance. An integrated research paradigm involving the three major steps of selecting, describing, and optimizing these independent variables is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Williges and Williges (1989) proposed a paradigm for sequential research in human factors that involves the three-step approach shown on this slide.…”
Section: Sequentialmentioning
confidence: 99%
See 4 more Smart Citations
“…Williges and Williges (1989) proposed a paradigm for sequential research in human factors that involves the three-step approach shown on this slide.…”
Section: Sequentialmentioning
confidence: 99%
“…For example, there were 14 potential factors to consider in designing the harmonic structure of the speech output system. Step 1 in the Williges and Williges (1989) paradigm summarized on a previous slide dealt with selecting the major independent variables that would be investigated through sequential experimentation. Both nonexperimental and experimental procedures were used to select these independent variables.…”
Section: Sequentialmentioning
confidence: 99%
See 3 more Smart Citations